HYBRID COMPRESSION OF MEDICAL IMAGES BASED ON GEOMETRIC REGULARITIES USING NSC-BANDELET TRANSFORM - Rajesh Kanna P (International Journal of Advanced Science and Technology, 2020)
An approach to provide more enhanced compression model is proposed in this work. The work integrates the betterments of both orthogonal base regular function and geometric regularity through the proposed NSC- Bandelet compression model. The models remove the noise elements in the source image and capture the geometric regularity of the image’s edges. The model use SPIHT encoder for better encoding. The model was analyzed for its performance against the existing models for PSNR, SSIM and compression ratio. The results show that the model does perform better in all the metrics analyzed.